Re-channelling Nigerian energy resources for economic revival : the proceedings of the Third International energy forum organised by International energy services limited held in Lagos, Nigeria between 31st May-2nd June, 1995 - Fawibe, Oladiran; International Energy Services Limited (Lagos, Nigeria : International Energy Services Ltd., 1996)
The book is the proceedings of the Third International energy forum organised by International energy services limited held in Lagos, Nigeria between 31st May-2nd June, 1995 with lots of discussions on energy resources in Nigeria.
Includes bibliographical references and index.
rua 06/03/15
Loans
Keywords: Petroleum industry and trade; Energy policy